Community Behavior in Responding to Seasonal Flooding in Jantur Village, Kutai Kartanegara Regency - Findi Findi; Juwari Juwari; Aisyah Trees Sandy; Rahmadi Rahmadi; Tarisa Mirda Sofiana (JPG (Jurnal Pendidikan Geografi), 2026)
Seasonal flooding is a recurring disaster that affects riverbank communities, particularly settlements located in lowland areas along major river and lake systems. Jantur Village, Muara Muntai District, Kutai Kartanegara Regency, is one of the areas that experiences seasonal flooding almost every year because of its geographical position near the Mahakam River and Lake Jempang. This condition has shaped how local communities prepare for, respond to, and recover from flood events. This study aims to analyze community behavior in responding to seasonal flooding in Jantur Village by focusing on three phases: before, during, and after flooding, while also considering demographic characteristics, livelihood dependence, and Banjar river culture. This research used a descriptive qualitative approach. Data were collected through in-depth interviews, field observations, and documentation. Respondents were selected using purposive sampling, involving 30 residents who had lived in the area for at least ten years and had direct experience with seasonal flooding. The data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The results show that before flooding, residents carried out preparedness actions by monitoring rainfall and river water levels, securing valuables in higher places, preparing reusable wood to build temporary elevated floors, and preparing boats for mobility. During flooding, residents demonstrated emergency response behavior by evacuating vulnerable family members, using boats as transportation, protecting household assets, sharing mobility access through kinship and neighbor networks, and strengthening mutual assistance. After the flood receded, residents conducted recovery activities by cleaning houses and surroundings, repairing damaged facilities, dismantling and storing wooden platforms, and strengthening house structures as long-term adaptation. These findings indicate that the behavior of the Jantur community reflects social, economic, cultural, and physical adaptation patterns formed through repeated flood experience, local knowledge, Banjar river-based practices, and collective resilience.